Patient satisfaction: an indicator of quality in disablement services centres. Issue 1 (March 1995) - Smith, C; McCreadie, M; Unsworth, J; Wickings, H I; Harrison, A
Abstract : OBJECTIVES–To develop a patient satisfaction system for disablement services centres and to report on how the initial findings have been used in audit to improve their quality of care and services. DESIGN–Interview survey of randomly selected users attending in three centres: Birmingham (centre X), Oxford (centre Y), and Cambridge (centre Z) to establish core topics for developing a patient satisfaction questionnaire with incorporation into a computer patient satisfaction system (PATSAT) to enable collation of responses to the questionnaire. A pilot of the questionnaire was undertaken in the centres to assess the sensitivity of the questionnaire, which was subsequently used as part of clinical audit process during June 1991 and April 1992 in centre X and the patient satisfaction system used to monitor changes in routine practice. PATIENTS–123 amputees in the development phase, selected by cluster sampling, and 1103 amputees in the pilot study. MAIN MEASURES–Satisfaction scores for components of the service. RESULTS–The questionnaire included 16 core topics contributing to quality of care and services, including comfort of limbs, appointments, interpersonal aspects of care, a system of support and counselling, and organisation. The pilot survey demonstrated high satisfaction scores for aspects of interpersonal care, organisation, and physical surroundings of the centres and lower satisfaction for counselling services, comfort of the limb and the number of alterations made before the limb was considered acceptable. During the audit in centre X these results prompted changes to care and services which produced significant improvements in satisfaction. CONCLUSIONS–The early results suggest that the questionnaire, coupled with PATSAT software system, enable users' views to be expressed, collated, and fed back to staff; the information provided has already prompted change, and the system is sufficiently sensitive to measure changes in satisfaction with the service.